RECRUITMENT, TRAINING AND EMPLOYEE PRODUCTIVITY IN NIGERIAN CUSTOMS SERVICE - Dan, Idris Sule; Ayodele, Nwaodike Chibuzor; Abiodun, Oni Michael (Jurnal Studi Pemerintahan, 2020)
The productivity of the Nigeria Customs Service (NCS) has ripple effect on all the sectors of the Nigeria economy and this is because the Customs is considered a policy instrument for enforcing trade policies and enhancing growth of domestic economy through boarder protection. However, the performance of the NCS has experienced a decline in unit of transactions recorded from 2015-2019 and had frustrated the ease of business transactions in Nigeria. These challenges has been attributed to the recruitment procedure, training and development. Hence, this study examined the recruitment, training and employee productivity in the Nigeria customs service. A mixed research design was adopted with a population of 7,347 officers and men of the NCS. A sample size of 383 was computed through Krejcie and Morgan sample-size determination formula. The study adopted the stratified random sampling to select the officers and men of the NCS in Abuja and Lagos command units from three management cadres.Â  Questionnaire and interview guide were the instrument of data collection. Response rate of 87.7% was achieved, and data were analyzed and presented through descriptive and inferential statistics. Findings revealed that recruitment and selection had significant effect on employee productivity (R2 = 0.054; Î²= 0.189; t= 4.385 p< 0.05); training and Development had significant effect on employee productivity (R2 = 0.100; Î²= 0.269; t= 6.086; p< 0.05) in the Nigeria Customs Service. This study concluded that human resources management practices had weak effect on employee productivity in the NCS.